Screening of Blood Donors for Transfusion Transmitted Infections in Tertiary Care Hospital of Faisalabad - Sarwat Jahan; Saira Mushtaq; Farah Amir Ali (Aziz Fatimah Medical and Dental College, 2019)
Background: Blood transfusion saves millions of lives worldwide each year and reduces morbidity but at the same time is a source for potentially life threatening transfusion transmissible infections (TTIs). These TTIs are a threat to blood safety. Sensitive screening with advanced technologies reduces the risk of TTIs, but it still remains a major concern. Objective of this study was to determine the frequencies of various ABO blood groups and to screen the TTIs like Hepatitis B (HBV), Hepatitis C (HCV), Human Immunodeficiency Virus (HIV), Syphilis and Malaria among voluntary and replacement blood donors of Faisalabad. Methodology: This cross sectional study was conducted at Aziz Fatimah Hospital Faisalabad, from July 2018 to November 2018. After taking informed consent all replacement and voluntary blood donors were screened for HCV, HBV, HIV, syphilis and malaria. Results: During 5 months of study period, total 1942 patients, of age ranged 18-40 years, were screened for TTIs. All blood donors were male; no female came to donate blood during this duration. Highest percentage of study population were blood group B (36.9%), followed by blood group O (28.1), A (22.2%), and AB (9.2%) respectively. Frequencies and percentages of Rhesus blood groups exhibited the predominance of positive rhesus groups in the study population. Out of total donors, 78 (4%) were infected with HCV, 30 (1.5%) with HBV, 10 (0.5%) with HIV, 19 (1 %) with syphilis and 3(0.20%) were seropositive for Malaria. Therefore, 140 (7.2 %) blood donors out of total were seropositive for various TTIs. Conclusion: This study showed the seroprevalence of transfusion transmitted infections (TTIs) among the blood donors. Highest percentage of blood donors suffered from HCV, followed by HBV, syphilis, HIV and malaria.